Obstacles That Prevent Economics Education from Being Integrated for Sustainable Development - Nehemiah Wokji, Gotip (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
The study looked at the obstacles that stand in the way of Economics Education's smooth integration with sustainable development. Based on a thorough analysis of case studies and literature, the study pinpoints the primary roadblocks preventing advancement in this field. The academic standards with disciplines, the issue of interdisciplinarity, change resistance, and economics and teacher education are some of the challenges that have been identified. The report suggests various strategic options to overcome these obstacles. These include, among other things, redesigning the economics curriculum, implementing active learning techniques, and taking a multidisciplinary approach that combines ideas from several academic fields, such as political science, sociology, environmental science, and ethics, to provide students with a thorough understanding of sustainability issues.